Board of Directors and ICT Governance: A New Paradigm for Corporate Relations - A. S . Yukhno (Управленческие науки)
The following paper’s research subject is to determine the role of the board of directors of an organization in the framework of information and communication technologies governance (hereinafter — ICT governance) at a company’s digital transformation stage. The article aims to study and identify trends and features of ICT governance, taking Russian and foreign experience into account. Methods of generalization, synthesis, comparative analysis of up-to-date approaches are used in the paper to outline the role of the board of directors during a period of dynamic technological changes in the company and factors increasing its ICT governance effectiveness. The author summarizes and analyzes the ICT governance specifics, including the features of its application, the necessary organizational changes, as well as the main tasks of the board of directors in this domain, which determines the scientific novelty of the study. The effectiveness of ICT governance exercised by the board of directors is considered by the author as an assessment criterion of a company’s readiness for digital transformation and a necessary tool to ensure that members of the boards of directors perform their duties. It is concluded that it depends on many factors and requires considering various organization specifics and its development strategy on a case-by-case basis. The research results may be relevant for the Russian corporate practice and further studies in this area.